The generational tourist - Gorenak, Mitja (Mednarodno inovativno poslovanje, 2025)
Purpose of the article –The purpose of this article is to explore the correlation between generational values and tourism product selection. It addresses the scientific problem of how socio-historical experiences influence consumer behaviour in the tourism sector. The goal is to identify distinct patterns among Baby Boomers, Generation X, and Generation Y that affect travel preferences, including price sensitivity, trip duration, travel style, and desired levels of autonomy.Research methodology –A two-step research methodology was applied. In the first step, a codebook was created based on the catalogue of trips from a cooperating travel agency. Trips were categorised by seven characteristics such as type, length, and autonomy. In the second step, a dataset of 9605 travellers was analysed using SPSS 24. Generational cohorts were determined based on age, and correlation and cross-tabulation analyses were conducted to uncover significant patterns.
Keywords: consumer behaviour; generacijske skupine; generacijske vrednote; generational cohorts; generational values; izbira turističnega produkta; potovalne preference; potrošniško vedenje; tourism product selection; travel preferences; Turisti; Turizem